From Molecular Reconstruction of Mesoscopic Functional Conductive Silk Fibrous Materials to Remote Respiration Monitoring. Issue 26 (26th May 2020) - Ma, Liyun; Liu, Qiang; Wu, Ronghui; Meng, Zhaohui; Patil, Aniruddha; Yu, Rui; Yang, Yun; Zhu, Shuihong; Fan, Xuwei; Hou, Chen; Li, Yanran; Qiu, Wu; et al.
Abstract: Turning insulating silk fibroin materials into conductive ones turns out to be the essential step toward achieving active silk flexible electronics. This work aims to acquire electrically conductive biocompatible fibers of regenerated Bombyx mori silk fibroin (SF) materials based on carbon nanotubes (CNTs) templated nucleation reconstruction of silk fibroin networks. The electronical conductivity of the reconstructed mesoscopic functional fibers can be tuned by the density of the incorporated CNTs. It follows that the hybrid fibers experience an abrupt increase in conductivity when exceeding the percolation threshold of CNTs >35 wt%, which leads to the highest conductivity of 638.9 S m −1 among organic‐carbon‐based hybrid fibers, and 8 times higher than the best available materials of the similar types. In addition, the silk‐CNT mesoscopic hybrid materials achieve some new functionalities, i.e., humidity‐responsive conductivity, which is attributed to the coupling of the humidity inducing cyclic contraction of SFs and the conductivity of CNTs. The silk‐CNT materials, as a type of biocompatible electronic functional fibrous material for pressure and electric response humidity sensing, are further fabricated into a smart facial mask to implement respiration condition monitoring for remote diagnosis and medication. Abstract : A new conceptual silk meso‐fibrous material for biocompatible electronic applications is developed by carbon nanotubes meso reconstruction. It can be adopted to fabricate various fibrous sensors, i.e., electronic humidity sensors. In combination with internet of things (IoTs) and artificial intelligence technologies, a remote respiratory condition monitoring and diagnosis can be achieved.